Fuentes de información de América Latina : repertorio selectivo y anotado de enciclopedias, diccionarios, bibliografías, repertorios biográficos, catálogos, guías, anuarios, índices, bases de datos, etc. : 1964-2008 - Geoghegan, Abel Rodolfo (Biblioteca Alfagrama., 2011)
El propósito del repertorio Fuentes de Información de América Latina ¿1964-2008 es presentar una guía selectiva y anotada que facilite : 1) el conocimiento y el acceso a información general y especializada que se utiliza corrientemente en la investigación y el estudio por parte de especialistas, profesores, estudiantes universitarios, bibliotecarios, especialistas en información y de toda persona que concurre a una biblioteca o centro de información para documentarse. 2) la identificación de fuentes de informacion básicas que permitan el acceso a información sobre temas generales y especializados de las humanidades y las ciencias sociales y de las ciencias puras y aplicadas. 3) la identificación y conocimiento de fuentes de información elaboradas y editadas (en forma impresa o en soporte electrónico) a partir del año 1964, en los principales países y en los diversos idiomas de América Latina, de los Territorios del Mar Caribe, de Europa y, además, de las fuentes editadas en los Estados Unidos y en países de otras regiones geográficas, que permiten el acceso a información que necesita y debe utilizar el investigador y el especialista de América Latina. The guide we are presently publishing represents a continuation and comprehensive up-to-date version of Obras de referencia de America Latina (Buenos Aires, 1965. xxiii, 280 p.) edited with the sponsorship of Unesco, on the basis of a favourable recommendation of its International Consulting Committee on Bibliography, Documentation and Terminology. The purpose of Fuentes de información de America Latina, 1964-2008 [Latin American Source, 1964-2008] (in 2 v.) is to provide a selective and annotated guide that can contribute to: 1- The knowledge and access to general and specialized information that is currently used in study and research by specialist, professors, university students, librarians, information specialists and any person who is seeking documentation. 2- The identification of basic information sources that provide an access to general and specialized subjects in the humanities and social sciences and in the pure and applied sciences. 3- The identification and knowledge of information source produced and published (in book form or in an electric format) since year 1964, in basic countries and in the diverse languages of Latin America and the Caribbean region and Europe, and sources published in the united State and countries of other geographic regions that provide and access to information that is needed and used by Latin American research and specialists. The guide we are presently includes over 15000 information sources of different types: encyclopedias, general and specialized dictionaries, general and specialized bibliographies, bibliographic catalogues, library catalogues, periodical catalogues and indexes, biographical dictionaries, guide, yearbooks, geographic atlases, indexes, data bases, etc.